Análise da gestão de custos interorganizacionais na transferência de tecnologia em empresas parceiras - Machado, Sabrina Porto (2024)
The study aims to analyze how the institutionalization of inter-organizational cost management helps in the transfer of technology in partner companies. Qualitative and descriptive research, carried out based on a multiple case study, due to the interest in analyzing a specific and replicated reality, considering the formation of partnerships for Technology Transfer. The evidence was collected from directors, managers, coordinators and developers of Information Technology and Business Intelligence (BI) developers from units that make up a credit cooperative. The theoretical relationships between the constructs were analyzed through evidence collected in interviews divided into categories, involving the crossing of responses in the search for understanding practices and strategies for transferring technologies in partner companies, as well as initiatives and decisions in cost management strategies. interorganizational in the formation of partnerships, and the Institutionalization of Processes demonstrating the rules for preparing, implementing and operating technologies. Based on the evidence collected, the vision of each respondent was diagnosed through a representative sample, observing cultural change and the evolutionary perception in relation to technology. As proposals for future studies, it is suggested to expand the understanding of technology transfer and process management between other partner cooperatives.